Effects of Trichinella spiralis and its excretory/secretory products on autophagy of host muscle cells in vivo and in vitro. - Xiaoxiang Hu; Xiaolei Liu; Xue Bai; Li Yang; Jing Ding; Xuemin Jin; Chen Li; Yulu Zhang; Yanfeng Li; Yong Yang; Mingyuan Liu (Public Library of Science (PLoS), 2021)
Trichinella spiralis (T. spiralis) is a widely distributed pathogenic microorganism that causes trichinellosis, a disease that has the potential of causing severe harm to their host. Numerous studies have demonstrated that autophagy can be triggered by microbial infection, such as bacteria, viruses, protozoa, and parasitic helminths. However, it's still unknown whether autophagy can facilitate host resistance to T. spiralis infection. The present study examined the role of autophagy in striated muscle cell transformation following infection with T. spiralis in BALB/c mice. Transmission electron microscopy (TEM) was used to detect the production of the host diaphragm autophagosome after T. spiralis infection, and changes in the protein and transcriptional levels of autophagic marker proteins were also detected. The significance of autophagy in T. spiralis infection, namely inhibition of T. spiralis growth, was preliminarily evaluated by conducting in vivo experiments using autophagy inhibitors. Besides, we studied the effect of excretory-secretory products (ES) of T. spiralis on autophagy of C2C12 myoblasts. The changes in protein and gene expression levels in autophagy-related pathways in vitro and in vivo were measured as further evidence. The results showed that T. spiralis infection induced autophagy in the host muscle cells. Meanwhile, ES inhibited autophagy of myoblasts in vitro, but this did not affect the cell viability. The upregulation and downregulation of autophagy-related factors in skeletal muscle cells may indicate an adaptive mechanism providing a comfortable niche for the parasite.